Perkumpulan Sekar Rukun: Perjuangan Pemuda Sunda Masa Pergerakan Nasional (1919-1931) - Ar Razy, Mohammad Refi Omar (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2021)
This study aims to analyze the kirprah of the Sekar Rukun Association during the National Movement (1919-1931) which includes the formation, form of struggle, and the process of merging with the Young Indonesia organization. The research method used is the historical method which consists of heuristic, source criticism, interpretation, and historiography stages. Through this research, it can be seen that, first, the Sekar Rukun Association was formed by Sundanese figures who attended school in Batavia, such as Doni Ismail, Iki Adiwidjaja, Djuwariah, Hilman, Moh. Sapii, Mangkudiguna, Soetisna Sendjaja and Iwa Kusumasumantri before finally Dr. Husein Djajadiningrat was involved in the Sekar Rukun Association. Second, the form of struggle for the Sekar Rukun Association is by working with youth organizations similar to that during the National Movement such as Jong Java, Jong Ambon, Jong Sumatranen Bond, Jong Islamieten Bond, Jong Celebes, Jong Bataks and so on. One form of the struggle of the Sekar Rukun Association together with other youth organizations was to hold Youth Congresses I and II in 1926 and 1928. The 2nd Youth Congress in 1928 was known as the Youth Pledge event. Third, as a form of unity and integrity, the Sekar Rukun Association merged with the other youth organizations mentioned above to form an organization called Young Indonesia in 1931.